2010
DOI: 10.1158/0008-5472.can-09-4479
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Fibroblast Growth Factor Receptors Blocks PI3K/AKT Signaling, Induces Apoptosis, and Impairs Mammary Tumor Outgrowth and Metastasis

Abstract: Members of the fibroblast growth factor receptor (FGFR) family have essential roles in normal physiology and in cancer where they control diverse processes. FGFRs have been associated with breast cancer development. Thus, models to study the role of FGFR in breast cancer and their targeting potential are important. We present an in vitro and in vivo analysis of FGFRs in the breast cancer model cell lines 67NR and 4T1. We show that both tumor cell lines coexpress FGFRs and ligands and display autocrine FGFR sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
151
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(166 citation statements)
references
References 45 publications
12
151
2
1
Order By: Relevance
“…10). Although challenging the signalling dogma holding that the GTPase-dependent stimulation of PI3Ka is mostly mediated by direct physical interactions with oncogenic Ras proteins 33 , these results are consistent with previous data indicating that the PI3Ka/Akt axis can be activated in Ras-independent manners in some Ras-transformed cells 16,24,[34][35][36][37] . Interestingly, the influence of R-Ras2 on the PI3K/Akt pathway is highly dependent on the experimental conditions used.…”
Section: R-ras2 Deficient Tumours Develop Compensatory Mechanismssupporting
confidence: 91%
See 1 more Smart Citation
“…10). Although challenging the signalling dogma holding that the GTPase-dependent stimulation of PI3Ka is mostly mediated by direct physical interactions with oncogenic Ras proteins 33 , these results are consistent with previous data indicating that the PI3Ka/Akt axis can be activated in Ras-independent manners in some Ras-transformed cells 16,24,[34][35][36][37] . Interestingly, the influence of R-Ras2 on the PI3K/Akt pathway is highly dependent on the experimental conditions used.…”
Section: R-ras2 Deficient Tumours Develop Compensatory Mechanismssupporting
confidence: 91%
“…These cells represent good tools to address functional redundancy issues, because they exhibit constitutive activation of classical Ras proteins due to the presence of either oncogenic mutations (MDA-MB-231-Luc cells) 22,23 or autocrine signalling loops (4T1 cells) 24 . These cell lines also differ in metastatic potential, thus facilitating the use of both gain-and loss-of-function approaches to analyse the role of R-Ras2 in this process 25 .…”
Section: R-ras2 Affects Primary Tumorigenesis Of Breast Cancer Cellsmentioning
confidence: 99%
“…Accordingly, the expression of FGFR1 and FGFR2 is partially regulated by E2F1 (Tashiro et al, 2003;Kanai et al, 2009). Furthermore, targeting FGFR-mediated signaling that acts in an autocrine manner in a subset of breast cancers of poor prognosis has been shown to impair tumor outgrowth and metastasis (Dey et al, 2010). These data, together with observations linking FGFR2 and risk of breast cancer (Easton et al, 2007;Hunter et al, 2007;Meyer et al, 2008), further support that FGFR-mediated signaling is central in breast carcinogenesis.…”
Section: Effect Of 17be2 Through Eramentioning
confidence: 72%
“…Akt1 expression is associated with cell survival, growth, and migration in cancer, 26,27 and a decrease in p-AKT expression levels due to Akt1 knockdown considerably affects cell proliferation. 29 We found that the proliferation of the A549 cells was inhibited by the overexpression of miR-9500 compared with the overexpression of the NC (Figures 4a and b).…”
Section: Discussionmentioning
confidence: 99%
“…23,24 The primary regulator of the PI3K pathway is Akt, a protein kinase B that mediates cell survival, cell death, 25 cell growth, cell migration and angiogenesis. [26][27][28] The silencing of the Akt1 gene has been shown to inhibit the proliferation of gastric cancer cells both in vitro and in vivo. 29 Other studies have shown that aberrant AKT activation has a critical role in tumorigenesis.…”
mentioning
confidence: 99%